Evaluation for an Open Society: Then and Now - Robert Picciotto (Journal of MultiDisciplinary Evaluation)
Background: Karl Popper’s views about science and political economy remain relevant to evaluation theory and practice. His Open Society opus inspired pioneering contributions to experimental evaluation and shaped the evaluation discipline. Yet, his ideas are not widely known without the evaluation community even though populist leaders are once again threatening to undermine democracy.